Analisis Penerapan SIMAPAN pada Kementerian Investasi dan Hilirisasi/BKPM - Ahmad Zidan; Tri Hesti Utaminingtyas; Gentiga Muhammad Zairin (LPPM Universitas Negeri Jakarta, 2025)
This study aims to analyze the implementation of SIMAPAN BKPM at Ministry of Investment and Downstream and its contribution to enchance transparency, accountability, and effectiveness in state budget management as part of supporting the Sustainble Development Goals (SDGs) 16. This study used a qualitative approach with a case study method through in-depth interviews with four informants that directly involved in the budget management process, that is the Head of Finance Division, The PPSPM, the Verificator, and The Finance Administrator. The data collected through interviews, limited observation, and analysis of internal documents, and relevant regulations. The results indicate that SIMAPAN BKPM strenghthens transparency through real-time monitoring of SPP status, enchances accountability through multi0layer verification mechanism between verificator and PPSPM, and supports effectiveness of the budget disbursment process. However, SIMAPAN BKPM has not fully supporting public information disclosure as the system is used solely for internal purposes. Overall, SIMAPAN BKPM positively contributes to the achievemnt of SDG 16, particulary in strenghtening effective, accountabily, and transparent instituitions.